2009
DOI: 10.1007/s12274-009-9008-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved peptidyl linkers for self-assembly of semiconductor quantum dot bioconjugates

Abstract: We demonstrate improved peptide linkers which allow both conjugation to biomolecules such as DNA and self-assembly with luminescent semiconductor quantum dots. A hexahistidine peptidyl sequence was generated by standard solid phase peptide synthesis and modified with the succinimidyl ester of iodoacetamide to yield a thiol-reactive iodoacetyl polyhistidine linker. The reactive peptide was conjugated to dye-labeled thiolated DNA which was utilized as a model target biomolecule. Agarose gel electrophoresis and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…20 We, and others, have demonstrated that a variety of QDs can be self-assembled with proteins and peptides expressing clearly available (His) n -sequences in a rapid manner (<30 min) due to the high-affinity equilibrium binding constants of this solution interaction ( K d −1 ~1 nM). 20,21,2629 Importantly, control can be exercised over the ratio or valence of molecules assembled per QD through the molar equivalents utilized. We have previously shown that DNA sequences terminally-modified with (His) n -peptidyl sequences can also self-assemble to QDs in the same manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 We, and others, have demonstrated that a variety of QDs can be self-assembled with proteins and peptides expressing clearly available (His) n -sequences in a rapid manner (<30 min) due to the high-affinity equilibrium binding constants of this solution interaction ( K d −1 ~1 nM). 20,21,2629 Importantly, control can be exercised over the ratio or valence of molecules assembled per QD through the molar equivalents utilized. We have previously shown that DNA sequences terminally-modified with (His) n -peptidyl sequences can also self-assemble to QDs in the same manner.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that DNA sequences terminally-modified with (His) n -peptidyl sequences can also self-assemble to QDs in the same manner. 21,30 Here, we exploit aniline-catalyzed hydrazone ligation chemistry to join the modified backbone DNA to a (His) 6 -peptidyl sequence (Figure 1B). The Dawson lab has shown that this coupling reaction is characterized by enhanced bioconjugation rates of 10 1 – 10 3 M −1 s −1 in mild, aqueous conditions (slightly acidic to neutral pH) and can reach equilibrium ( K eq = 2.3×10 6 M −1 ) in under 30 min using 100 mM aniline catalyst with 10 µM of reactants.…”
Section: Resultsmentioning
confidence: 99%
“…2), were synthesized from PNA monomers followed by the addition of three 2-(2-aminoethoxy)ethoxy acetic acid (eg1) groups on an Expedite 8909 Nucleic Acid Synthesis System (Applied Biosystems, Life Technologies, Carlsbad, CA, USA) using the standard manufacturer's protocols for Fmoc chemistry (2-lmol scale). Iodoacetate was added to the third eg1 group on the linker by reacting the resin-bound PNA strand with 2 mM N-succinimidyl iodoacetate by the method of Berti and coworkers [26]. Biotin was added to the third eg1 group of the linker on another PNA strand with complementary base sequence using 2 mM (+)-biotin Nhydroxysuccinimide ester (Alfa Aesar, Ward Hill, MA, USA) as described by Guerasimova [27].…”
Section: Synthesis Of Pna Duplex Probementioning
confidence: 99%
“…Improved NP and biomolecule chemistries allowing for orthogonal attachment of proteins and other (bio) molecules as desired with control over number and orientation need to be pursued [114]. Beyond what is currently utilized, several established and developing chemistries are available to draw from, including self-assembly driven by polyhistidine or other peptidyl sequences [24,115,116], various chemoselective ligations [117,118], and the family of 'click' cycloaddition and related chemistries [119] to name but a Expert Opin. Drug Deliv.…”
Section: Expert Opinionmentioning
confidence: 99%